Performance of DcMFC-AnMBR coupled system for the treatment of sulfadiazine-containing swine wastewater - SIMA Cong; ZHANG Xinbo; CHENG Yanbin; WANG Huizhong; DU Qing; ZHONG Lingling; Huu Hao NGO (Gongye shui chuli)
A dual-chamber microbial fuel cell-anaerobic membrane bioreactor(DcMFC-AnMBR) coupled process system was constructed. The power production, pollutant removal, and gas generation performance of the coupled system for treating swine wastewater containing sulfadiazine(SDZ) was investigated, and the change of membrane pollution characteristics under the influence of SDZ was also analyzed. The results showed that in the presence of 1.0 mg/L SDZ, the average output voltage and coulombic efficiency of the DcMFC-AnMBR coupled system decreased by 6.11% and 7%, respectively. The maximum power density of the coupled system was 35.34 mW/m2, the COD removal rate remained at 98%, and the average biogas production was 542.59 mL/d. Meanwhile, the presence of SDZ increased the absolute value of Zeta potential of sludge mixture by 25.83%, the average particle size of sludge decreased by 14-16 µm, and the average concentrations of soluble microbial products(SMP) and extracellular polymers(EPS) increased by 7.76% and 35.43%, respectively. The transmembrane pressure(TMP) was consistently near zero during the operation of the coupled process system. The cause of membrane fouling mitigation in coupled systems could be attributed to the oxidative degradation of SMP and EPS by electroactive microorganisms.